Persimmon tannin modified bio-based composite adsorption material and preparation method thereof

By covalently combining amino-modified persimmon tannin with aldehyde-modified cellulose through Schiff base condensation reaction, the problems of poor structural stability and easy loss of active components in bio-based adsorbent materials are solved, achieving efficient adsorption and recycling, improving the adsorption performance of heavy metal ions and organic dyes, and possessing the function of slow release of rare earth elements.

CN121669183APending Publication Date: 2026-03-17GUANGXI ACAD OF SCI +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202610179264.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-02-09
Publication Date
2026-03-17

AI Technical Summary

Technical Problem

Existing bio-based adsorption materials suffer from poor structural stability, easy loss of active components, and insufficient adsorption efficiency, making it difficult to achieve efficient adsorption and recycling.

Method used

Aminated persimmon tannins are covalently bonded to aldehyde-modified cellulose via Schiff base condensation reaction to form a persimmon tannin-modified bio-based composite adsorbent material. The high adsorption activity of persimmon tannins and the porous framework structure of cellulose enhance the stability and adsorption performance of the material.

Benefits of technology

It achieves stable immobilization of active components, improves adsorption efficiency and material recyclability, enhances adsorption of heavy metal ions and organic dyes, and possesses slow-release properties of rare earth elements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121669183A_ABST
    Figure CN121669183A_ABST
Patent Text Reader

Abstract

The invention discloses a persimmon tannin modified bio-based composite adsorption material and a preparation method thereof, and belongs to the technical field of water pollution treatment, metal element loading and bio-based materials. The preparation comprises aminated persimmon tannin and aldehyde cellulose. Persimmon tannin is subjected to amination modification to introduce amino groups, cellulose is subjected to oxidation modification to generate aldehyde groups, the amino groups and the aldehyde groups react in a weak acid environment to form imine bonds and generate covalent binding, the persimmon tannin is anchored on a cellulose porous framework, and the problem that the persimmon tannin is lost along with water flow in the adsorption process of water treatment is avoided; and in the adsorption process, metal ions and organic matters in the water body can be captured through chelating of phenolic hydroxyl groups in persimmon tannin. In addition, the porous structure of the cellulose contains a large number of adsorption active sites, and the contact probability of the active sites is increased, so that the adsorption efficiency is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the technical fields of water pollution control, metal element loading and bio-based materials, specifically relating to a persimmon tannin-modified bio-based composite adsorbent material and its preparation method. Background Technology

[0002] With the rapid development of industrial manufacturing, such as electroplating, printing and dyeing, and chemical industries, the production of heavy metal ions, such as Pb, has become increasingly important. 2+ Cu 2+ The discharge of industrial wastewater containing cationic organic dyes continues to increase. These pollutants are characterized by high toxicity, difficulty in degradation, and easy bioaccumulation. Once they enter the aquatic environment, they will not only disrupt the balance of aquatic ecosystems but also endanger human health through the food chain. Therefore, the efficient treatment of such pollutants in water bodies has become an important issue in the field of environmental governance.

[0003] Loading of metallic elements, such as rare earth elements, and their slow release, has wide applications in agriculture and industry. Effectively loading rare earth elements can achieve slow release in soil, improving the efficiency of agricultural production, and is an important research direction in industry.

[0004] Among numerous wastewater treatment and metal loading technologies, adsorption has become one of the mainstream technologies for treating heavy metal and organic dye pollution due to its advantages such as simple operation, high treatment efficiency, and relatively low cost. Bio-based adsorbent materials, with their wide availability of raw materials (such as tannins and cellulose derived from agricultural and forestry waste), good environmental compatibility, and biodegradability, are gradually replacing traditional inorganic adsorbent materials such as activated carbon and zeolite, becoming a research hotspot in this field.

[0005] However, existing bio-based adsorbent materials still have significant technical limitations in practical applications. On the one hand, the performance of a single bio-based adsorbent component is insufficient. For example, although persimmon tannin is rich in phenolic hydroxyl groups and has a strong adsorption capacity for heavy metal ions and organic dyes, its high water solubility makes it easily lost with water flow, leading to a rapid decline in adsorption efficiency and potentially causing secondary pollution. On the other hand, while pure cellulose has a porous structure and good mechanical stability, making it suitable as an adsorbent carrier, it lacks effective adsorption sites, resulting in extremely low adsorption efficiency when used alone. Existing technologies have not yet solved the problems of easy loss of active components, poor structural stability, and the difficulty in balancing adsorption efficiency and recyclability in bio-based adsorbent materials.

[0006] Therefore, developing a bio-based composite adsorbent material that can stably immobilize active components, retain high adsorption performance, and be reusable has become a technological direction that urgently needs to be broken through in this field. Summary of the Invention

[0007] The purpose of this application is to overcome the technical defects of existing bio-based adsorbent materials, such as poor structural stability, easy loss of active components, and insufficient adsorption efficiency, and to provide a persimmon tannin-modified bio-based composite adsorbent material and its preparation method. By modifying persimmon tannin and cellulose, the two are covalently bonded by Schiff base condensation reaction. This not only retains the high-efficiency adsorption activity of persimmon tannin, but also improves the structural stability of the material by relying on the porous framework of cellulose, thereby achieving simultaneous optimization of adsorption performance and recycling capacity.

[0008] To achieve the above objectives, this application adopts the following technical solution:

[0009] In a first aspect, the present invention provides a method for preparing a persimmon tannin-modified bio-based composite adsorbent material, comprising the following steps:

[0010] Aminated persimmon tannin and aldehyde-modified cellulose were prepared according to the specified ratio, dispersed in deionized water, stirred and mixed, and the pH of the system was adjusted with an acid reagent. Then the temperature was raised to react. After the reaction was completed, the mixture was filtered, washed with deionized water, and then dried to obtain persimmon tannin-modified bio-based composite adsorbent material.

[0011] The aminoated persimmon tannin is prepared by persimmon tannin and an amination agent;

[0012] The aldehyde-modified cellulose is prepared from cellulose and an oxidizing agent.

[0013] Furthermore, the mass ratio of amino-modified persimmon tannin to aldehyde-modified cellulose is (6-7):(3-4).

[0014] Furthermore, the pH of the system is adjusted to 4-5 with an acid reagent; the acid reagent includes one or more of hydrochloric acid or acetic acid; the concentration of the acid reagent is 0.1-1 mol / L.

[0015] Furthermore, the total mass ratio of amino-modified persimmon tannin and aldehyde-modified cellulose to the volume ratio of deionized water is 1 g:(10-20) ml; the stirring conditions are: temperature 25-35℃, speed 150-250 rpm, time 20-40 min; the heating reaction conditions are: temperature 50-70℃, speed 300-500 rpm, time 2-4 h; washing with deionized water until the pH of the washing solution is 6.5-7.5; the drying conditions are: drying at 60-80℃ for 3-5 h.

[0016] Furthermore, the preparation steps of amino-modified persimmon tannin include:

[0017] Disperse persimmon tannin in deionized water at a mass ratio of 1:(5-10), stir at 150-200 rpm for 10-30 min at 30-50℃, add amination agent, and continue to react at 150-250 rpm for 1-2 h.

[0018] After the reaction was completed, the solution was dialyzed with a deionized water semipermeable membrane until the pH reached 6.8-7.2, and then freeze-dried under vacuum at -40℃ to -80℃ to obtain amino-modified persimmon tannin.

[0019] Furthermore, the mass ratio of persimmon tannin to amination agent is 1:(0.3-0.8).

[0020] Furthermore, the amination agent includes one or more of ethylenediamine, propylenediamine, or p-phenylenediamine.

[0021] Furthermore, the preparation steps of aldehyde-modified cellulose include:

[0022] Cellulose is dispersed in deionized water at a mass ratio of 1:(8-15), stirred at 300-400 rpm for 0.5-1 h at 35-55℃, and then an oxidant is added. The reaction is continued at 300-400 rpm for 1-2.5 h.

[0023] After the reaction is complete, wash and filter repeatedly with deionized water 3-5 times, and then dry at 60-80℃ for 4-8 hours to obtain the product.

[0024] Furthermore, the mass ratio of cellulose to oxidant is 1:(0.5-1.2); the oxidant includes one or more of sodium periodate or potassium periodate.

[0025] Secondly, the present invention provides a persimmon tannin-modified bio-based composite adsorbent material prepared using the aforementioned preparation method.

[0026] This application discloses a bio-based composite adsorbent material modified with persimmon tannin, comprising aminated persimmon tannin and aldehyde-modified cellulose. The persimmon tannin is modified using an amination agent to introduce amino groups into its molecular chain as sites for cross-linking reactions. The cellulose is oxidized using an oxidizing agent to generate aldehyde groups on its surface, which are then used to covalently bond with the amino groups of the aminated persimmon tannin.

[0027] Secondly, amino-modified persimmon tannin and aldehyde-modified cellulose are dispersed in an aqueous system. The reaction environment is adjusted using an acid reagent, promoting a Schiff base condensation reaction between the amino groups of the amino-modified persimmon tannin and the aldehyde groups of the aldehyde-modified cellulose, forming covalent imine bonds. In an acidic environment of pH 4-5, the amino groups on the surface of the amino-modified persimmon tannin remain in a free state, enhancing its nucleophilic reactivity. Furthermore, the weakly acidic conditions reduce the protonation of the imine bonds, inhibiting the reverse reaction of imine bond hydrolysis. This connection method overcomes the drawback of easy separation of components in physical mixing, anchoring the persimmon tannin on the porous cellulose framework. This avoids the loss of persimmon tannin with water flow during adsorption and allows the phenolic hydroxyl groups of the persimmon tannin to be dispersed on the framework.

[0028] When the composite adsorbent material is put into the water, the persimmon tannin anchored on the cellulose framework forms a chelating effect with heavy metal ions and interacts with cationic organic dyes, thus efficiently capturing pollutants. The porous cellulose framework provides stable support for the adsorption process, and its rich pore structure can also promote the contact between pollutants and the adsorption sites of persimmon tannin, thereby increasing the adsorption rate.

[0029] Beneficial technical effects:

[0030] This application discloses a bio-based composite adsorbent material modified with persimmon tannin, comprising aminated persimmon tannin and aldehyde-modified cellulose. While persimmon tannin is rich in phenolic hydroxyl groups and possesses natural adsorption potential for metal ions and organic dyes, its inherent water solubility makes it prone to detachment during water adsorption, leading to a rapid decline in adsorption efficiency and potential secondary pollution from tannin release. After amination modification, amino groups are introduced into the persimmon tannin molecular chain, while the phenolic hydroxyl groups remain intact. Instead, they achieve uniform dispersion through covalent bonding with cellulose, fully exposing the adsorption active sites and increasing the likelihood of binding with the aldehyde groups of cellulose. After oxidative modification, cellulose not only forms reaction sites for binding with persimmon tannin but also retains its porous structure, providing skeletal support for the adsorption process and promoting pollutant diffusion through its abundant pores, increasing the contact opportunities between pollutants and active sites. During the adsorption stage, the phenolic hydroxyl groups in persimmon tannins capture pollutants such as metal ions and organic dyes in the water through chelation. In addition, the porous structure of cellulose contains a large number of adsorption active sites. The presence of these sites increases the probability of contact between pollutants and active sites, thereby improving the adsorption efficiency. Attached Figure Description

[0031] Figure 1 A flowchart illustrating a persimmon tannin-modified bio-based composite adsorbent material and its preparation method;

[0032] Figure 2 The graph shows the slow-release curves of a persimmon tannin-modified bio-based composite adsorbent prepared in Example 3 for different rare earth ions.

[0033] Figure 3 Infrared characterization images of persimmon tannin and amino-modified persimmon tannin in a persimmon tannin-modified bio-based composite adsorbent material prepared in Example 3;

[0034] Figure 4 Infrared characterization images of cellulose, aldehyde-modified cellulose, and composite adsorbent in a persimmon tannin-modified bio-based composite adsorbent prepared in Example 3;

[0035] Figure 5 The image shows an infrared characterization of a persimmon tannin-modified bio-based composite adsorbent material prepared in Example 3 and its application in the adsorption of lead, cerium, lanthanum, copper and methylene blue.

[0036] Figure 6 The image shows a comparison of (a) and (b) before and after the adsorption of methylene blue by the persimmon tannin-modified bio-based composite adsorbent material prepared in Example 3.

[0037] Figure 7 SEM and EDS images of a persimmon tannin-modified bio-based composite adsorbent material prepared in Example 3 are shown, where (a) is the SEM image, (b) is the combined elemental EDS image, (c) is the C elemental image, (d) is the N elemental image, and (e) is the O elemental image.

[0038] Figure 8 The images show SEM and EDS images of cerium adsorbed by a persimmon tannin-modified bio-based composite adsorbent material prepared in Example 3, where (a) is the SEM image, (b) is the combined elemental EDS image, (c) is the C elemental image, (d) is the O elemental image, (e) is the N elemental image, and (f) is the Ce elemental image.

[0039] Figure 9 The images show SEM and EDS images of lanthanum adsorption by a persimmon tannin-modified bio-based composite adsorbent material prepared in Example 3, where (a) is the SEM image, (b) is the combined elemental EDS image, (c) is the C elemental image, (d) is the N elemental image, (e) is the O elemental image, and (f) is the La elemental image. Detailed Implementation

[0040] To make the above-mentioned objectives, features and advantages of this application more apparent and understandable, a detailed description of specific embodiments of this application will be provided below.

[0041] Many specific details are set forth in the following description in order to provide a full understanding of this application. However, this application may also be implemented in other ways different from those described herein. Those skilled in the art can make similar extensions without departing from the spirit of this application. Therefore, this application is not limited to the specific embodiments disclosed below.

[0042] Example 1

[0043] like Figure 1 As shown, this embodiment provides a persimmon tannin-modified bio-based composite adsorbent material and its preparation method, including the following steps:

[0044] Preparation of amino-modified persimmon tannin: Persimmon tannin was dispersed in deionized water at a mass ratio of 1:5. The mixture was stirred at 180 rpm for 20 min at 30 °C until it was uniformly dispersed. Then, p-phenylenediamine was added at a mass ratio of 1:0.3. The mixture was stirred at 200 rpm at 40 °C for 1.5 h. After the reaction was completed, the mixture was dialyzed through a deionized water semi-permeable membrane to pH 6.8 and then freeze-dried under vacuum at -40 °C to obtain amino-modified persimmon tannin.

[0045] Preparation of aldehyde-modified cellulose: Cellulose was dispersed in deionized water at a mass ratio of 1:8. After stirring at 220 rpm for 0.7 h at 35 °C, sodium periodate was added at a mass ratio of 1:0.5. The mixture was stirred at 350 rpm for 1.8 h at 45 °C. After the reaction was completed, the mixture was washed and filtered three times with deionized water and dried at 70 °C for 6 h to obtain aldehyde-modified cellulose.

[0046] Preparation of composite adsorbent material: Aminated persimmon tannin and aldehyde-modified cellulose were dispersed together in deionized water at a mass ratio of 6:4, wherein the total mass of amino-modified persimmon tannin and aldehyde-modified cellulose to the volume ratio of deionized water was 1 g: 10 ml. The mixture was stirred at 200 rpm at 30 °C for 30 min. The pH of the system was adjusted to 4.5 with 0.5 mol / L hydrochloric acid, and the temperature was raised to 60 °C. The mixture was stirred at 400 rpm for 3 h. After the reaction was completed, the mixture was filtered, washed with deionized water until the pH of the washing solution was 7.0, and then dried at 70 °C for 4 h to obtain persimmon tannin-modified bio-based composite adsorbent material.

[0047] Example 2

[0048] like Figure 1 As shown, this embodiment provides a persimmon tannin-modified bio-based composite adsorbent material and its preparation method, including the following steps:

[0049] Preparation of amino-modified persimmon tannin: Persimmon tannin was dispersed in deionized water at a mass ratio of 1:10. The mixture was stirred at 150 rpm for 15 min at 25 °C until it was uniformly dispersed. Then, propylene diamine was added at a mass ratio of 1:0.8. The mixture was stirred at 150 rpm for 1 h at 30 °C. After the reaction was completed, the mixture was dialyzed through a deionized water semi-permeable membrane to pH 7.2 and then freeze-dried under vacuum at -80 °C to obtain amino-modified persimmon tannin.

[0050] Preparation of aldehyde-modified cellulose: Cellulose was dispersed in deionized water at a mass ratio of cellulose to deionized water of 1:15. After stirring at 200 rpm for 0.5 h at 30 °C, potassium periodate was added at a mass ratio of cellulose to potassium periodate of 1:1.2. The mixture was stirred at 300 rpm for 1 h at 35 °C. After the reaction was completed, the mixture was washed and filtered four times with deionized water and dried at 60 °C for 4 h to obtain aldehyde-modified cellulose.

[0051] Preparation of composite adsorbent material: The above-mentioned amino-modified persimmon tannin and aldehyde-modified cellulose were dispersed in deionized water at a mass ratio of 7:3, wherein the total mass of amino-modified persimmon tannin and aldehyde-modified cellulose to the volume ratio of deionized water was 1g:20ml. The mixture was stirred at 150rpm at 25℃ for 25min. The pH of the system was adjusted to 3.0 with 0.1mol / L acetic acid, and the temperature was raised to 50℃. The mixture was stirred at 300rpm for 2h. After the reaction was completed, the mixture was filtered, washed with deionized water until the pH of the washing solution was 6.5, and then dried at 60℃ for 3h to obtain the persimmon tannin-modified bio-based composite adsorbent material.

[0052] Example 3

[0053] like Figure 1 As shown, this embodiment provides a persimmon tannin-modified bio-based composite adsorbent material and its preparation method, including the following steps:

[0054] Preparation of amino-modified persimmon tannin: Persimmon tannin was dispersed in deionized water at a mass ratio of 1:7.5. The mixture was stirred at 200 rpm for 25 min at 35 °C until it was uniformly dispersed. Then, ethylenediamine was added at a mass ratio of 1:0.55. The mixture was stirred at 250 rpm for 2 h at 50 °C. After the reaction was completed, the mixture was dialyzed through a deionized water semi-permeable membrane to pH 7.0 and then freeze-dried under vacuum at -60 °C to obtain amino-modified persimmon tannin.

[0055] Preparation of aldehyde-modified cellulose: Cellulose was dispersed in deionized water at a mass ratio of cellulose to deionized water of 1:11.5. After stirring at 250 rpm for 1 h at 40 °C, sodium periodate was added at a mass ratio of cellulose to sodium periodate of 1:0.85. The mixture was stirred at 400 rpm for 2.5 h at 55 °C. After the reaction was completed, the mixture was washed and filtered four times with deionized water and dried at 80 °C for 8 h to obtain aldehyde-modified cellulose.

[0056] Preparation of composite adsorbent material: Aminated persimmon tannin and aldehyde-modified cellulose were dispersed together in deionized water at a mass ratio of 6.5:3.5, wherein the total mass of amino-modified persimmon tannin and aldehyde-modified cellulose to the volume ratio of deionized water was 1 g:15 ml. The mixture was stirred at 250 rpm at 35 °C for 35 min. The pH of the system was adjusted to 6.0 with 1.0 mol / L hydrochloric acid, and the temperature was raised to 70 °C. The mixture was stirred at 500 rpm for 4 h. After the reaction was completed, the mixture was filtered, washed with deionized water until the pH of the washing solution was 7.5, and then dried at 80 °C for 5 h to obtain persimmon tannin-modified bio-based composite adsorbent material.

[0057] Figure 2The graph shows the slow-release curves of a persimmon tannin-modified bio-based composite adsorbent material prepared in this embodiment for different rare earth ions. It presents the variation of the content of four element ions (La, Ce, Pr, and Nb) in the eluent with the number of rinsing cycles. Four rinsing cycles were performed, and the vertical axis represents the ion content. The four curves of different colors in the graph correspond to the four ions respectively. It can be seen that with the increase of the number of rinsing cycles, the content of all ions shows a significant decreasing trend. The ion content is the highest during the first rinsing, and the rate of decrease gradually slows down during subsequent rinsing processes. This intuitively reflects that the rinsing operation has a good removal effect on these four ions, and the increase of the number of rinsing cycles helps to further reduce the residual ion content in the eluent.

[0058] Figure 3 The image shows the infrared characterization of persimmon tannin and amino-modified persimmon tannin in the persimmon tannin-modified bio-based composite adsorbent prepared in this embodiment. The composite adsorbent and dry potassium bromide (KBr) were thoroughly ground and mixed at a ratio of 1:100 using the potassium bromide pelleting method. The wavelength range of the measured FT-IR spectra was 400-4000 cm⁻¹. -1 The infrared spectrum of persimmon tannins is at 3380 cm⁻¹. -1 At this point, a characteristic peak appears, corresponding to the characteristic adsorption peak of -OH. After amination, it appears at 1252 cm⁻¹. -1 The appearance of a stretching vibration peak, corresponding to the absorption characteristic peak of CN, indicates that persimmon tannin has been successfully amination.

[0059] Figure 4 The image shows the infrared characterization of cellulose, aldehyde-modified cellulose, and the composite adsorbent in the persimmon tannin-modified bio-based composite adsorbent prepared in this embodiment. The composite adsorbent and dry potassium bromide (KBr) were thoroughly ground and mixed uniformly at a ratio of 1:100 using the potassium bromide pelleting method. The wavelength range of the measured FT-IR spectra was 400-4000 cm⁻¹. -1 1058cm -1 The stretching vibration absorption peak at 1161 cm⁻¹ corresponds to the cellulose skeleton. -1 The absorption vibration peak of the primary alcohol hydroxyl groups on cellulose is 1112 cm⁻¹. -1 This is the adsorption vibration peak for secondary alcohols in cellulose. Aldehyde-modified cellulose shows a peak at 1681 cm⁻¹. -1 A small peak indicating stretching vibration was observed at 1621 cm⁻¹, which is a characteristic absorption peak of -CHO, indicating that cellulose was oxidized to aldehyde cellulose by sodium periodate. The infrared spectrum of the composite adsorbent was observed at 1621 cm⁻¹. -1 A stretching vibration peak was observed, which is a characteristic absorption peak of imine, indicating that the composite adsorbent was successfully synthesized.

[0060] Figure 5The infrared characterization images of the persimmon tannin-modified bio-based composite adsorbent prepared in this embodiment and its application in the adsorption of lead, cerium, lanthanum, copper, and methylene blue are shown. Comparing the infrared spectra of the adsorbent before and after adsorption, it can be found that at 553 cm⁻¹... -1 The stretching vibration of C-Br can be observed at 468 cm⁻¹, indicating that PbBr₂ is adsorbed by the adsorbent. -1 Ce-O stretching vibrations were detected, which is attributed to the adsorption of cerium nitrate by the composite adsorbent. Comparison of the infrared spectra before and after lanthanum nitrate adsorption revealed a chemical shift in C=O, with a peak at 1517 cm⁻¹. -1 The adsorption rate at this point showed a significant decrease, which is attributed to the interaction between lanthanum and C=O. In the adsorption of copper nitrate samples by the composite adsorbent, the concentration at 1518 cm⁻¹ was significantly reduced. -1 A chemical shift occurs at the C=O region, indicating that copper interacts with C=O. This is accompanied by the appearance of multiple peaks, suggesting the formation of various complex bonds in the adsorption of copper nitrate by the composite adsorbent. In the infrared spectrum of the sample adsorbing methylene blue, at 887 cm⁻¹... -1 SOC stretching vibrations can be observed at the site, indicating that methylene blue has been successfully adsorbed by the composite adsorbent.

[0061] Figure 6 The images show a comparison of the persimmon tannin-modified bio-based composite adsorbent material prepared in this embodiment before (a) and after (b) adsorption of methylene blue. The color depth decreased significantly, indicating that the composite adsorbent has great application potential for adsorbing and removing methylene blue.

[0062] Figure 7 The images show the SEM and EDS images of the persimmon tannin-modified bio-based composite adsorbent prepared in this embodiment. (a) SEM image, (b) combined elemental EDS image, (c) C elemental image, (d) N elemental image, and (e) O elemental image. The energy dispersive spectroscopy results indicate that the composite adsorbent is mainly composed of C, N, and O elements, with no other impurities detected, indicating that the synthesized composite adsorbent has high purity. Furthermore, the SEM image of the composite adsorbent shows that it has a macroporous blocky structure, which is beneficial for mass transfer of the adsorbate and allows it to reach adsorption equilibrium in a short time.

[0063] Figure 8 The images show SEM and EDS images of cerium adsorbed by the persimmon tannin-modified bio-based composite adsorbent material prepared in this embodiment. (a) SEM image, (b) combined EDS elemental map, (c) C elemental map, (d) O elemental map, (e) N elemental map, and (f) Ce elemental map. The energy dispersive spectroscopy (EDS) of the sample with adsorbed Ce showed the presence of Ce, while the composite adsorbent did not contain Ce, indicating that cerium nitrate was adsorbed by the composite adsorbent.

[0064] Figure 9The images show SEM and EDS images of lanthanum adsorption by a persimmon tannin-modified bio-based composite adsorbent material prepared in this embodiment. (a) SEM image, (b) combined EDS elemental map, (c) C elemental map, (d) N elemental map, (e) O elemental map, and (f) La elemental map. Lanthanum was also detected in the sample that adsorbed lanthanum, indicating that lanthanum was adsorbed onto the surface of the composite adsorbent.

[0065] Example 4

[0066] like Figure 1 As shown, this embodiment provides a persimmon tannin-modified bio-based composite adsorbent material and its preparation method, including the following steps:

[0067] Preparation of amino-modified persimmon tannin: Persimmon tannin was dispersed in deionized water at a mass ratio of 1:8. The mixture was stirred at 170 rpm for 18 min at 32 °C until uniformly dispersed. Propylene diamine was then added at a mass ratio of 1:0.6. The mixture was stirred at 220 rpm at 45 °C for 1.8 h. After the reaction was completed, the mixture was dialyzed through a deionized water semi-permeable membrane to pH 6.8 and then freeze-dried under vacuum at -80 °C to obtain amino-modified persimmon tannin.

[0068] Preparation of aldehyde-modified cellulose: Cellulose was dispersed in deionized water at a mass ratio of 1:13 and stirred at 230 rpm for 0.8 h at 38 °C. Sodium periodate was then added at a mass ratio of 1:0.9. The mixture was stirred at 380 rpm for 2.2 h at 48 °C. After the reaction was completed, the mixture was washed and filtered five times with deionized water and dried at 75 °C for 7 h to obtain aldehyde-modified cellulose.

[0069] Preparation of composite adsorbent material: Aminated persimmon tannin and aldehyde-modified cellulose were dispersed together in deionized water at a mass ratio of 6.2:3.4, wherein the total mass of amino-modified persimmon tannin and aldehyde-modified cellulose to the volume ratio of deionized water was 1 g:17 ml. The mixture was stirred at 230 rpm at 32 °C for 32 min. The pH of the system was adjusted to 5.0 with 0.6 mol / L acetic acid, and the temperature was raised to 65 °C. The mixture was stirred at 450 rpm for 3.5 h. After the reaction was completed, the mixture was filtered, washed with deionized water until the pH of the washing solution was 7.2, and then dried at 75 °C for 4.5 h to obtain persimmon tannin-modified bio-based composite adsorbent material.

[0070] Comparative Example 1

[0071] Comparative Example 1 provides a method for preparing a bio-based composite adsorbent material modified with persimmon tannin. Compared with Example 1, which did not prepare aminated persimmon tannin but only added persimmon tannin, the other operation steps and process parameters are the same as those in Example 1.

[0072] Comparative Example 2

[0073] Comparative Example 1 provides a method for preparing a persimmon tannin-modified bio-based composite adsorbent material. Compared to Example 1, which does not use aldehyde-modified cellulose, only cellulose is added, and other operating steps and process parameters are the same as in Example 1.

[0074] The performance of the persimmon tannin-modified bio-based composite adsorbent materials prepared in Examples 1-4 and Comparative Examples 1-2 was tested, and the performance test results are shown in Tables 1-3.

[0075] Test method:

[0076] 1. Adsorption capacity: Using the static adsorption method, Pb of certain concentrations were prepared. 2+ Cu 2+ Heavy metal ion solution, methylene blue organic dye solution and La 3+ Ce 3+ Rare earth ion solution; add a quantitative amount of composite adsorbent to the above solution, and oscillate at room temperature until adsorption equilibrium is reached. Measure the ion concentration in the solution before and after adsorption using inductively coupled plasma optical emission spectrometry (ICP-OES). Adsorption amount = (initial concentration of target substance in the solution before adsorption - remaining concentration of target substance in the solution after adsorption equilibrium) × solution volume ÷ mass of composite adsorbent added, and calculate the adsorption amount.

[0077] 2. Removal rate after adsorption-desorption cycle: After adsorption equilibrium, the material adsorbing pollutants / rare earth ions is placed in the corresponding desorbent, such as dilute hydrochloric acid solution, and shaken to desorb. After washing and drying, the adsorption-desorption operation is repeated 5 times. After each adsorption, the concentration of the target substance in the solution is determined according to the adsorption amount method. Removal rate = (initial concentration of target substance in solution before adsorption - residual concentration of target substance in solution after the 5th adsorption equilibrium) ÷ initial concentration of target substance in solution before adsorption × 100%. The removal rate data after the 5th cycle is recorded.

[0078] 3. Release of Rare Earth Elements: The release performance of the persimmon tannin-modified bio-based composite adsorbent material after loading rare earth elements was tested. 0.03 g of the composite adsorbent material loaded with rare earth elements was placed in a beaker, 100 ml of distilled water was added, and the mixture was stirred for 0.5 h. After centrifugation, the rare earth element content of the supernatant was measured. Another 50 ml of distilled water was added to the solid, stirred, and poured into a beaker. Another 50 ml of distilled water was added, and the above operation was repeated. The concentration of rare earth elements in the supernatant was measured each time to obtain elution data.

[0079] Table 1. Pollutant adsorption performance test results of the persimmon tannin-modified bio-based composite adsorbent materials prepared in Examples 1-4 and Comparative Examples 1-2.

[0080]

[0081] Table 2. Test results of rare earth element adsorption performance of the persimmon tannin-modified bio-based composite adsorbent materials prepared in Examples 1-4 and Comparative Examples 1-2.

[0082]

[0083] Table 3. Rare earth element release performance test results of the persimmon tannin-modified bio-based composite adsorbent material prepared in Example 3.

[0084]

[0085] Examples 1-4 all involved introducing reactive amino groups through persimmon tannin amination modification and generating aldehyde groups through cellulose oxidation modification. A weakly acidic environment was then used to promote Schiff base condensation reactions, forming stable imine covalent bonds, thus constructing a structure of adsorption active components and a porous framework. Experimental results showed that when used for pollutant adsorption, Pb... 2+ Adsorption capacity reaches 260-340 mg / g, Cu 2+ The adsorption capacity is 210-260 mg / g, and the methylene blue adsorption capacity is 170-220 mg / g. After 5 adsorption-desorption cycles, the removal rate remains at 81%-87%. When used for rare earth element adsorption, La... 3+ Adsorption capacity reaches 200-260 mg / g, Ce 3+ Adsorption capacity 195-250 mg / g, Pr 3+ Adsorption capacity 175-230 mg / g, Nd 3+ The adsorption capacity was 185-243 mg / g, and the removal rate remained at 79%-86% after 5 adsorption-desorption cycles. The core reason is that the covalent bonding not only prevented the persimmon tannin from being lost with the water flow, but also allowed its phenolic hydroxyl groups to be fully exposed. At the same time, the porous structure of cellulose accelerated the mass transfer and diffusion of pollutants, thus optimizing the adsorption performance and structural stability. Among them, Example 3 had the best compatibility between modification and crosslinking parameters, the most complete degree of crosslinking, and the best performance indicators.

[0086] Comparative Example 1 did not undergo amination modification of persimmon tannins, thus lacking reaction sites for interaction with aldehyde-modified cellulose. This prevented the formation of effective covalent bonds, and the tannins adhered to the cellulose surface solely through physical mixing, leading to significant detachment of persimmon tannins during adsorption and a severe shortage of adsorption sites. When used for pollutant adsorption, Pb... 2+ The adsorption capacity was only 85 mg / g, and the removal rate plummeted to 15% after 5 cycles; when used for rare earth element adsorption, Pr 3+ With an adsorption capacity of only 50 mg / g, the removal rate plummeted to 12% after 5 cycles, fully demonstrating the necessity of persimmon tannin amination modification for achieving strong component binding and ensuring adsorption performance.

[0087] Comparative Example 2, without aldehyde modification of cellulose, could not undergo a Schiff base reaction with aminodimethicone. Simply combining aminodimethicone with unmodified cellulose through physical mixing failed to achieve stable anchoring of the methicone, and the porous structure lacked numerous adsorption active sites, leading to easy leaching of the methicone and easy aggregation of the adsorption sites. When used for pollutant adsorption, Pb... 2+ The adsorption capacity is only 120 mg / g, and the removal rate after circulation is only 22%; when used for rare earth element adsorption, Pr 3+ With an adsorption capacity of only 75 mg / g and a removal rate of only 19% after cycling, the aldehyde modification of cellulose highlights the core role of cellulose in constructing a stable composite structure and enhancing adsorption performance.

[0088] Table 3 shows the rare earth element release performance test results of the persimmon tannin-modified bio-based composite adsorbent material prepared in Example 3. The results indicate that in four rare earth leaching experiments, La... 3+ The cumulative elution volume reached 50.9 mg / L, Ce 3+ The cumulative elution volume reached 45.0 mg / L, Pr 3+ The cumulative elution volume reached 41.1 mg / L, Nd 3+ The cumulative elution volume reached 49.2 mg / L. The elution data showed that the persimmon tannin-modified bio-based composite adsorbent material has good release function and is feasible as a carrier for the sustained release of potential rare earth elements.

[0089] It should be noted that the above embodiments are only used to illustrate the technical solutions of this application and are not intended to limit it. Although this application has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of this application without departing from the spirit and scope of the technical solutions of this application, and all such modifications and substitutions should be covered within the scope of the claims of this application.

Claims

1. A method for preparing persimmon tannin-modified bio-based composite adsorbent material, characterized by, The method comprises the following steps: The amino persimmon tannin and the aldehyde-based cellulose are taken according to the proportion, and then the two are dispersed in deionized water. After stirring and mixing, the pH of the system is adjusted by using an acid reagent, and then the reaction is carried out by heating. After the reaction is completed, filtration is carried out, and then washing is carried out with deionized water, and then drying treatment is carried out, so as to obtain the modified persimmon tannin bio-based composite adsorption material; The amino persimmon tannin is prepared from persimmon tannin and an amine reagent. The aldehyde-based cellulose is prepared from cellulose and an oxidizing agent.

2. The method for preparing persimmon tannin-modified bio-based composite adsorbent material according to claim 1, characterized by, The mass ratio of the amino persimmon tannin to the aldehyde-based cellulose is (6-7):(3-4).

3. The method for preparing a persimmon tannin-modified bio-based composite adsorbent material according to claim 1, characterized in that, The pH of the system is adjusted to 4-5 by using the acid reagent. The acid reagent includes one or more of hydrochloric acid and acetic acid. The concentration of the acid reagent is 0.1-1 mol / L.

4. The method for preparing a persimmon tannin-modified bio-based composite adsorbent material according to claim 1, characterized in that, The volume ratio of the total mass of the amino persimmon tannin and the aldehyde-based cellulose to the deionized water is 1 g:(10-20) ml. The stirring and mixing conditions are as follows: the temperature is 25-35 DEG C, the speed is 150-250 rpm, and the time is 20-40 min. The heating reaction conditions are as follows: the temperature is 50-70 DEG C, the speed is 300-500 rpm, and the time is 2-4 h. The deionized water is washed until the pH of the washing liquid is 6.5-7.

5. The drying treatment conditions are as follows: drying is carried out at 60-80 DEG C for 3-5 h.

5. The method for preparing a persimmon tannin-modified bio-based composite adsorbent material according to claim 1, characterized in that, The preparation steps of the amino persimmon tannin include the following steps: The persimmon tannin is dispersed in deionized water according to the mass ratio of 1:(5-10). After stirring at 150-200 rpm for 10-30 min at 30-50 DEG C, the amine reagent is added, and the reaction is continued at 150-250 rpm for 1-2 h. After the reaction is completed, semi-permeable membrane dialysis is carried out with deionized water until the pH is 6.8-7.

2. After vacuum freeze drying at -40 DEG C to -80 DEG C, the amino persimmon tannin is obtained.

6. The method for preparing a persimmon tannin-modified bio-based composite adsorbent material according to claim 5, characterized in that, The mass ratio of the persimmon tannin to the amine reagent is 1:(0.3-0.8).

7. The method for preparing a persimmon tannin-modified bio-based composite adsorbent material according to claim 5, characterized in that, The amine reagent includes one or more of ethylenediamine, propylenediamine and p-phenylenediamine.

8. The method for preparing a persimmon tannin-modified bio-based composite adsorbent material according to claim 1, characterized in that, The preparation steps of the aldehyde-based cellulose include the following steps: The cellulose is dispersed in deionized water according to the mass ratio of 1:(8-15). After stirring at 300-400 rpm for 0.5-1 h at 35-55 DEG C, the oxidizing agent is added, and the reaction is continued at 300-400 rpm for 1-2.5 h. After the reaction is completed, repeated washing and filtration are carried out 3-5 times with deionized water, and then drying is carried out at 60-80 DEG C for 4-8 h.

9. The method for preparing a persimmon tannin-modified bio-based composite adsorbent material according to claim 8, characterized in that, The mass ratio of the cellulose to the oxidizing agent is 1:(0.5-1.2). The oxidizing agent includes one or more of sodium periodate and potassium periodate.

10. A modified persimmon tannin bio-based composite adsorption material prepared by the preparation method according to any one of claims 1-9.

Citation Information

Patent Citations

  • Method for immobilizing phospholipase C by using magnetic tannic acid-chitosan particles as carrier

    CN114045280A

  • High-flux cellulose immobilized tannin membrane adsorption material as well as preparation method and application thereof

    CN120919982A

  • Water-insoluble tannin adsorbent and its production

    JP1995313870A